2023
DOI: 10.1002/adma.202305128
|View full text |Cite
|
Sign up to set email alerts
|

A Layered Bi2Te3@PPy Cathode for Aqueous Zinc‐Ion Batteries: Mechanism and Application in Printed Flexible Batteries

Abstract: Low‐cost, safe, and environmental‐friendly rechargeable aqueous zinc‐ion batteries (ZIBs) are promising as next‐generation energy storage devices for wearable electronics among other applications. However, sluggish ionic transport kinetics and the unstable electrode structure during ionic insertion/extraction hampers their deployment. Herein,  we propose a new cathode material based on a layered metal chalcogenide (LMC), bismuth telluride (Bi2Te3), coated with polypyrrole (PPy). Taking advantage of the PPy coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The calculated pseudocapacitance contributions at 0.2, 0.4, 0.6, 0.8, and 1 mV s –1 scan rates were 53%, 55%, 59%, 65%, and 71%, respectively (Figure S18). The above differences in charge storage contributions clearly uncover the factors behind the high rate performance of the V 2 O 3 /CNF electrode, as the capacitive contribution achieves a considerably swifter ionic storage even under high current densities …”
Section: Resultsmentioning
confidence: 94%
“…The calculated pseudocapacitance contributions at 0.2, 0.4, 0.6, 0.8, and 1 mV s –1 scan rates were 53%, 55%, 59%, 65%, and 71%, respectively (Figure S18). The above differences in charge storage contributions clearly uncover the factors behind the high rate performance of the V 2 O 3 /CNF electrode, as the capacitive contribution achieves a considerably swifter ionic storage even under high current densities …”
Section: Resultsmentioning
confidence: 94%
“…Previous studies suggested that the ions that intercalate into the defectfree Bi 2 Te 3 lattice are protons rather than Zn 2+ owing to the high energy barrier of Zn 2+ intercalation. [23] Herein, the participation of S dopant and Te vacancies evidently boosts the Zn 2+ adsorption ability, which activates the Zn 2+ insertion behavior for the SBT cathode. This finding might be attributed to the S dopant and Te vacancies decreasing the van der Waals' forces between Bi 2 Te 3 layers, which makes it easier to insert Zn 2+ into the SBT lattice.…”
Section: Charge Storage Mechanismmentioning
confidence: 88%
“…The twin problems of the energy crisis and environmental pollution have been the most serious challenges for the development of the global community in recent years. The main focus of research and development is on seeking a combination of theoretical research and experimentation to address these two major challenges, thereby realizing a new generation of more environmentally friendly energy technologies [ 1 , 2 , 3 , 4 ]. One focus is on the conversion and storage of clean energy, while lithium-ion battery (LIB) systems are one of the most anticipated energy storage devices [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%